Potential Use of Sea Water for Pineapple Production in BRIS Soil. - Musa, Mohamed Hanafi; Shahid, M. Shahidullah; Md. Niazuddin,; Abd Aziz, Zalilah; Mohammud, C. H. (2010)
An experiment was conducted to determine the response of four sea water treatments on an improved pineapple genotype “N- 36” grown in Beach Ridges Interspersed with Swales (BRIS) soil. Sea water treatments were prepared by substitution of K with Na ions i.e., 0% (in control), 15%, 30% and 60% of required K doses were replaced by Na ions from sea water. Treatment effects were non-significant up to 30% sodium replacement from sea water. Na replacement (60%) showed significant impact on different growth parameters at different stages (8-10 months after planting). However, the fruit yield, the final target of crop harvest was not adversely affected at significance level. Therefore, sea water irrigation can easily fulfil 60% dose of potassium fertilizer by sodium ions for the production of pineapple in BRIS soil.